2017
DOI: 10.1007/s11356-017-0681-z
|View full text |Cite
|
Sign up to set email alerts
|

Foliar application with nano-silicon reduced cadmium accumulation in grains by inhibiting cadmium translocation in rice plants

Abstract: Nano-silicon (Si) may be more effective than regular fertilizers in protecting plants from cadmium (Cd) stress. A field experiment was conducted to study the effects of nano-Si on Cd accumulation in grains and other organs of rice plants (Oryza sativa L. cv. Xiangzaoxian 45) grown in Cd-contaminated farmland. Foliar application with 5~25 mM nano-Si at anthesis stage reduced Cd concentrations in grains and rachises at maturity stage by 31.6~64.9 and 36.1~60.8%, respectively. Meanwhile, nano-Si application signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
65
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(68 citation statements)
references
References 37 publications
2
65
1
Order By: Relevance
“…The Si-NPs may improve the nutrients uptake by plants, which results in higher biomass. In this regard, Si-NPs increases the uptake of Mg, P, K and S contents in stressed plants [26,27]. Moreover, plant biomass may be remarkably improved by Si-NPs which might be due to its placement in the leaf bundle that affect the structure of chloroplasts and leaf yield at the unit level and therefore increase the plant's ability to use light [5].…”
Section: Biological Yield (By)mentioning
confidence: 99%
“…The Si-NPs may improve the nutrients uptake by plants, which results in higher biomass. In this regard, Si-NPs increases the uptake of Mg, P, K and S contents in stressed plants [26,27]. Moreover, plant biomass may be remarkably improved by Si-NPs which might be due to its placement in the leaf bundle that affect the structure of chloroplasts and leaf yield at the unit level and therefore increase the plant's ability to use light [5].…”
Section: Biological Yield (By)mentioning
confidence: 99%
“…Once absorbed, cadmium may remain toxic in ecosystems or human bodies for more than 20 years (Martelli et al, 2006a). On the other hand, cadmium is a highly mobile element, which is easy to be absorbed and accumulated by plants in cropland (Chen et al, 2018b;Sarwar et al, 2017). As a long term impact, cadmium may not only inhibited the yield and quality of crops seriously, but also enter human bodies through the food chain to accumulate and cause damage to human health (Liu et al, 2013;Shan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Several methods utilize an in situ application of amendments or immobilization agents to soils such as clay minerals, 2 biochar, 3,4 red mud [5][6][7] and iron-silicon material. 8 Another approach includes foliar spraying of liquid amendments as numerous studies have shown that the application of certain compounds containing Si, 9,10 Se, 11,12 or chitooligosaccharide, 13 could signicantly reduce Cd accumulation in plants. Alternatively, careful selection of low Cd-accumulating vegetable cultivars or pollution-safe cultivars was another effective strategy to reduce Cd uptake by vegetables and subsequent human exposure.…”
Section: Introductionmentioning
confidence: 99%